Data-Driven Public Management and Citizen Satisfaction Improvement Smart City Governance Frameworks: JEL Classification: H11; H83; O31; O38; R58 - Ethan Jonatan Chua (Generasi Sains Indonesia, 2026)
This research looks at how data-driven public management affects citizen satisfaction in the context of Singapore's smart city governance. This research is designed to provide an analysis of the relationship between the four components of digital responsiveness, data integration, evidence-based decision making and inter-agency coordination and the public perception of governance quality and administrative efficiency. Data from a survey of 250 users of digital public services in Singapore was used in a quantitative explanatory approach. Data was analyzed using descriptive statistics, classical assumption test, validity and reliability test, and multiple regression analysis. The results show that all dimensions of data-driven public management have a significant impact on citizen satisfaction. Digital responsiveness was the most important factor, followed by data integration, evidence-based decision making and inter-agency coordination. The findings suggest that the benefits of adopting integrated digital governance systems in smart cities include increased access to services, enhanced administrative efficiency, and greater public trust. The study also shows that, along with the use of technology, institutional coordination and citizen-centric governance are essential for successful smart governance. The results offer both theoretical and practical lessons for governments aiming to enhance sustainable and citizen-focused digital governance systems.